2006
DOI: 10.1371/journal.pbio.0040417
|View full text |Cite
|
Sign up to set email alerts
|

Polarised Asymmetric Inheritance of Accumulated Protein Damage in Higher Eukaryotes

Abstract: Disease-associated misfolded proteins or proteins damaged due to cellular stress are generally disposed via the cellular protein quality-control system. However, under saturating conditions, misfolded proteins will aggregate. In higher eukaryotes, these aggregates can be transported to accumulate in aggresomes at the microtubule organizing center. The fate of cells that contain aggresomes is currently unknown. Here we report that cells that have formed aggresomes can undergo normal mitosis. As a result, the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
209
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(219 citation statements)
references
References 46 publications
9
209
0
1
Order By: Relevance
“…Asymmetric segregation of IBs was demonstrated in previous studies, in particular using HttQ119 (12) (Fig. 2D), which forms insoluble IPODs (15).…”
Section: Junqs Are Asymmetrically Segregated During Mitosis In Mammaliansupporting
confidence: 74%
See 1 more Smart Citation
“…Asymmetric segregation of IBs was demonstrated in previous studies, in particular using HttQ119 (12) (Fig. 2D), which forms insoluble IPODs (15).…”
Section: Junqs Are Asymmetrically Segregated During Mitosis In Mammaliansupporting
confidence: 74%
“…This work sheds light on an important rejuvenation mechanism in mammalian cells and provides new biological insight into the role of inclusion bodies in regulating aggregation, toxicity, and aging. aggregate segregation during mammalian or Drosophila mitosis (12,13,14). The mechanism for directing misfolded proteins to different inclusions structures, however, appears to be at least partially conserved from yeast to mammals.…”
Section: Significancementioning
confidence: 99%
“…We therefore refer to juxtanuclear inclusions with mobile quality control substrates as JUNQs, and the polyQ Htt inclusions as IPODs, to distinguish between these distinct types of inclusion phenotypes. In particular, there is evidence that the accumulation of Htt in an IB is protective of cell viability (10, 13), whereas cytosolic Htt that fails to be sequestered in an IB is more toxic (22). Other experiments have suggested that familial ALS (fALS)-associated mutant SOD1 is most toxic when localized to an IB (8).…”
Section: Resultsmentioning
confidence: 99%
“…Examples include carbonylated protein sorting in yeast, mediated by actin filaments in a sir2p-dependent manner (27), the Shigella outer membrane protein IcsA (28), and other bacterial surface structure localization (29) as well as the microtubule-dependent aggrosome localization in mammalian cells (15). Intriguing is the similarity between aggrosome localization to the eukaryotic centrosome (18) and the inclusion bodies to the bacterial division plane. In the former model, putative stem cells exhibited a lower aggregation level as compared with differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, in vitro immunostaining of carbonylated proteins (16), correlated with aggregated proteins (17), revealed their retention in mother cells (16) although their in vivo dynamics and influence on aging could not be measured. Recently, the polarized asymmetric inheritance of aggrosomes in Drosophila melanogaster neuronal precursor cells as well as in epithelial crypts of patients suffering from the polyglutamine aggregationassociated ataxia type 3 disease was reported (18). Because the low number of inclusion bodies per bacterial cell (13) may lead to their asymmetric partitioning and because of their potential cellular toxicity, we investigated the hypothesis that asymmetric segregation of damaged proteins and their pole-biased accumulation may explain, at least in part, the observed pattern of E. coli aging.…”
mentioning
confidence: 99%